2013
DOI: 10.1136/heartjnl-2013-303811
|View full text |Cite
|
Sign up to set email alerts
|

Remote monitoring after recent hospital discharge in patients with heart failure: a systematic review and network meta-analysis

Abstract: STS HH and TM with medical support provided during office hours showed beneficial trends, particularly in reducing all-cause mortality for recently discharged patients with heart failure. Where 'usual' care is less good, the impact of RM is likely to be greater.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
133
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(136 citation statements)
references
References 46 publications
1
133
1
1
Order By: Relevance
“…2,17,18,21 To date, a few systematic reviews have been published on TCIs. [22][23][24] It has been shown that the interventions decrease hospital admissions after 12 months of follow-up.22 These reviews, however, were unable to determine the most efficacious TCI.22,24 They did not include all types of TCIs 22,23 ; furthermore, a substantial number of RCTs on these interventions have been published since the publication of the reviews (26 since that by Phillips et al 24 ). We therefore conducted a systematic review and meta-analysis to determine the impact of TCIs on the rate of all-cause readmission and ED visits by patients with CHF, and to identify the most effective TCIs and their optimal duration.…”
mentioning
confidence: 99%
“…2,17,18,21 To date, a few systematic reviews have been published on TCIs. [22][23][24] It has been shown that the interventions decrease hospital admissions after 12 months of follow-up.22 These reviews, however, were unable to determine the most efficacious TCI.22,24 They did not include all types of TCIs 22,23 ; furthermore, a substantial number of RCTs on these interventions have been published since the publication of the reviews (26 since that by Phillips et al 24 ). We therefore conducted a systematic review and meta-analysis to determine the impact of TCIs on the rate of all-cause readmission and ED visits by patients with CHF, and to identify the most effective TCIs and their optimal duration.…”
mentioning
confidence: 99%
“…U meta-analizi istraaeivanja ukljuËujuÊi viπe od 6.000 bolesnika, Pandor i sur. 35 su utvrdili da je telemonitoring nakon prijma u bolnicu bolesnika sa ZS bio povezan s boljim preaeivljavanjem, posebice tamo gdje je uobiËajena skrb bila manje dobra.…”
Section: Terapija Ure-ajima I Pra∆enje Telemonitoriranjeunclassified
“…It might be that targeted intensive monitoring during periods of high risk, such as immediately after hospital discharge, makes the best use of remote monitoring. In a meta-analysis of trials involving over 6,000 patients, Pandor et al 35 found that remote monitoring following an admission with heart failure was associated with improved survival, particularly where usual care was less good.…”
Section: Remote Monitoringmentioning
confidence: 99%
“…In a meta-analysis of trials involving over 6000 patients, Pandor et al (35) found that remote monitoring following an admission with heart failure was associated with improved survival, particularly where usual care was less good.…”
Section: Device Therapy and Monitoringmentioning
confidence: 99%